Problematics of Digital Literacy Implementation in Early Children at Nurul Aulia Kindergarten, Depok - Erna Budiarti (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The Covid 19 pandemic that occurred from the end of 2019 to 2021 has made all aspects of our lives undergo a complete change. Education is an important sector because of the change from the offline learning process (face-to-face) to bold learning (online). The problem is then due to the unpreparedness of the education stakeholders, schools, teachers, parents, and students. This condition is almost felt by all schools in Early Childhood Education (ECE). The purpose of the study is to determine how problematics and application of digital literacy are carried out in Nurul Aulia Kindergarten, Depok. This study employed a qualitative approach through phenomenological research design. The results showed that online learning for early childhood was felt to be less effective. This was due to the unpreparedness of the infrastructure and the superstructure in the Nurul Aulia Kindergarten, Depok.